Dynamic call admission control under partial separation in ATM networks. - Liu, Hui. (University of Ottawa (Canada), 2001)
A dynamic call admission control scheme is proposed for ATM networks to support multiple Quality of Service (QoS) requirements. The scheme is based on the notion of partial separation. It divides the overall traffic flows into classes, within which each traffic source has similar QoS requirements, but may have different traffic characteristics, and the bandwidth of a link is dynamically allocated among the classes. A dynamic bandwidth allocation strategy is introduced. It achieves the goal of bandwidth allocation by optimizing a cost function defined as an estimate of the overall cell loss rate that would be generated by the total offered load. It is dynamic in the sense that the bandwidth allocation is adjusted each time when a connection requires for an acceptance or a leave. While optimizing the overall cell loss rate across classes, cell level constraint is satisfied for each class by deploying the cell loss rate estimate algorithm, proposed by H. Esaki in Connection Admission Control in ATM Networks. A simulation program is developed to validate the accuracy of the algorithm. Extensive numerical and simulation results are presented. Numerical search method is deployed to locate the optimal bandwidth assignment set. Numerical results are presented to evaluate the efficiency and adequacy of the CAC scheme.
Keywords: Engineering, Electronics and Electrical.